Hadith #2722 - Sunan Abi Dawud - Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Isma'il bin Ayyash bin Saleem إسماعيل بن عياش بن سليم; Muhammad bin al-Walid al-Zubaidi محمد بن الوليد بن عامر الزبيدي; Sa'id bin al-'As bin Sa'id bin al-'As; Sa'id bin Mnswr bin Sh'bh سعيد بن منصور بن شعبة; Unbasa bin Sa'id bin al-Durays عنبسة بن سعيد بن الضريس (Sunan Abi Dawud)
At the battle of Badr the Messenger of Allah gave me AbuJahl’s sword, as I had killed him.
Grade: Da'if

Hadith #2855 - Sunan Abi Dawud - Abu Idrees al-Khulani أبو إدريس الخولاني; Baqiyya bin al-Walid bin Sa'aid بقية بن الوليد بن صائد; Muhammad bin al-Walid al-Zubaidi محمد بن الوليد بن عامر الزبيدي; Muhammad bin Harb al-Wasti محمد بن حرب بن حرمان النشائي; Yonus bin Syf يونس بن سيف (Sunan Abi Dawud)
I said: Messenger of Allah, I hunt with my trained dog, and with my untrained dog? He said: ‘What you hunt with your trained dog, mention Allah’s names (on it) and eat; and what you hunt with your untrained dog, and you find in a position that you slaughter it, then eat.
Grade: Sahih

Hadith #3319 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ma'mar bin Rashid معمر بن راشد; Muhammad bin al-Walid al-Zubaidi محمد بن الوليد بن عامر الزبيدي; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan Abi Dawud)
Ka’b ibn Malik said to AbuLubabah; or someone else whom Allah wished; or to the Prophet (ﷺ): To make my repentance complete I should depart from the house of my people in which I fell into sin, and that I should divest myself of all my property as sadaqah (alms). He said: A third (of your property) will be sufficient for you.
Grade: Hasan

Hadith #3521 - Sunan Abi Dawud - Abdullah bin 'Abdur Jabbar عبد الله بن عبد الجبار الخبائري زبريق; Abu Bakr bin 'Abdur Rahman أبو بكر بن عبد الرحمن بن الحارث بن هشام; Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Isma'il bin Ayyash bin Saleem إسماعيل بن عياش بن سليم; Muhammad bin al-Walid al-Zubaidi محمد بن الوليد بن عامر الزبيدي; Muhammad bin Awf bin Sufyan محمد بن عوف بن سفيان الطائي (Sunan Abi Dawud)
“If he paid something from the price (of the property), then he will be equal to the creditors in it.”
Grade: Sahih

Hadith #3738 - Sunan Abi Dawud - Baqiyya bin al-Walid bin Sa'aid بقية بن الوليد بن صائد; Muhammad bin al-Walid al-Zubaidi محمد بن الوليد بن عامر الزبيدي (Sunan Abi Dawud)
if one of you invites his brother, he should accept(the invitation), whether it is a wedding feast or something of that nature.
Grade: Sahih

Hadith #3803 - Sunan Abi Dawud - Abdur Rahman bin Abi 'Auf al-Jershy عبد الرحمن بن أبي عوف الجرشي; Muhammad bin al-Walid al-Zubaidi محمد بن الوليد بن عامر الزبيدي; Muhammad bin Harb al-Wasti محمد بن حرب بن حرمان النشائي (Sunan Abi Dawud)
The Messenger of Allah(ﷺ) prohibited the eating of every beast of prey with fang, and every bird with a talon.
Grade: Sahih

Hadith #3898 - Sunan Abi Dawud - Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Baqiyya bin al-Walid bin Sa'aid بقية بن الوليد بن صائد; Haywat bin Sharih bin Safwan حيوة بن شريح بن صفوان التجيبي; Muhammad bin al-Walid al-Zubaidi محمد بن الوليد بن عامر الزبيدي (Sunan Abi Dawud)
A man from Aslam tribe said: I was sitting with the Messenger of Allah (ﷺ). A man from among his Companions came and said: Messenger of Allah! I have been stung last night, and I could not sleep till morning. He asked: What was that? He replied: A scorpion. He said: Oh, had you said in the evening: “I take refuge in the perfect words of Allah from the evil of what He created,” nothing would have harmed you, Allah willing.
Grade: Sahih

Hadith #4057 - Sunan Abi Dawud - al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Amr bin 'Uthman عمرو بن عثمان بن عفان; Anas ibn Malik; Baqiyya bin al-Walid bin Sa'aid بقية بن الوليد بن صائد; Kathir bin 'Ubaid bin Nmyr كثير بن عبيد بن نمير المذحجي; Muhammad bin al-Walid al-Zubaidi محمد بن الوليد بن عامر الزبيدي (Sunan Abi Dawud)
The Prophet of Allah (ﷺ) took silk and held it in his right hand, and took gold and held it in his left hand and said: both of these are prohibited to the males of my community.
Grade: Sahih

Hadith #4634 - Sunan Abi Dawud - al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Amr bin 'Uthman عمرو بن عثمان بن عفان; Jabir ibn 'Abdullah; Muhammad bin al-Walid al-Zubaidi محمد بن الوليد بن عامر الزبيدي; Muhammad bin Harb al-Wasti محمد بن حرب بن حرمان النشائي (Sunan Abi Dawud)
One day the Prophet (ﷺ) said: Which of you had dream? A man said: It is I. I saw as though a scale descended from the sky. You and AbuBakr were weighed and you were heavier; AbuBakr and Umar were weighed and AbuBakr was heavier: Umar and Uthman were weighed and Umar was heavier; than the scale was taken up. we saw signs of dislike on the face of the Messenger of Allah (ﷺ).
Grade: Sahih